Values-led conservation - Jepson, P; Canney, S (Blackwell Publishing Ltd., 2003)
In international nature conservation policy, value-arguments based on science and economic rationalism increasingly overshadow the aesthetic and ethical arguments that originally inspired the conservation movement. We argue that this trend risks removing conservation from the public realm, in part because it facilitates the adoption by nongovernment conservation bodies of corporate values and/or their integration with government bureaucracies. By contrast, the explicit recognition of aesthetic and ethical values would complement arguments based on science and economic utility. We subscribe to a reformist view of globalization that accepts the inevitability of a globalizing world but argues that the process needs humanizing by incorporating quality of life values in the policy process. We argue that re-emphasis of aesthetic and ethical arguments in international conservation policy would contribute to this goal by reasserting links between conservation bodies and the public, thereby leading to more effective action on the ground.